Community Resistance Citizens Refuse Hotel Development in The Special Region of Yogyakarta - Sulistyaningsih, Sulistyaningsih; Muryanti, Muryanti; Agus Saputro; Kanita Khoirun Nisa (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2022)
The construction of hotels in the Special Region of Yogyakarta for the last 10 years has met with resistance among the public. This of course comes with reasons that are felt important by the community. The purpose of this paper is to find out the actors involved in the Resistance, the forms of resistance, and the reasons why people carried out resistance. This research method uses qualitative research methods. As for data collection through secondary data obtained through online mass media. The research findings show that: 1) The actors involved in this resistance are the community consisting of various layers, namely the people who are directly affected, and the people who are not directly affected. Apart from that, there are also NGO affiliations (such as One Name NGO). (2). Forms of resistance were carried out through real protest actions, either through demonstrations, installing banners, or drawing murals. (3) The reason for the community's resistance is due to more environmental aspects (social and environmental in general). There seems to be a social impact, and an environmental impact (environmental pollution, decreased water debit because water is sucked up for the benefit of the hotel).